Analysis of Synaptotagmin, SV2, and Rab3 Expression in Cortical Glutamatergic and GABAergic Axon Terminals - Bragina, Luca (Frontiers Research Foundation, 2012)
We investigated whether cortical glutamatergic and GABAergic release machineries can be differentiated on the basis of the nature and amount of proteins they express, by performing a quantitative analysis of the degree of co-localization of synaptotagmin (SYT) 1 and 2, synaptic vesicle protein 2 (SV2) A and B, and Rab3a and c in VGLUT1+, VGLUT2+, and VGAT+ terminals and synaptic vesicles (SVs) in rat cerebral cortex. Co-localization studies showed that VGLUT1 puncta had high levels of SV2A and B and of Rab3c, intermediate levels of SYT1, and low levels of SYT2 and Rab3c; VGLUT2 puncta exhibited intermediate levels of all presynaptic proteins studied; whereas vesicular GABA transporter (VGAT) puncta had high levels of SV2A and SYT2, intermediate levels of SYT1, Rab3a, and Rab3c, and low levels of SV2B. Since SV2B is reportedly expressed by glutamatergic neurons and we observed SV2B expression in VGAT puncta, we performed electron microscopic studies and found SV2B positive axon terminals forming symmetric synapses. Immunoisolation studies showed that the expression levels of the protein isoforms varied in the three populations of SVs. Expression of SYT1 was highest in VGLUT1–SVs, while SYT2 expression was similar in the three SV groups. Expression of SV2A was similarly high in all three SV populations, except for SV2B levels that were very low in VGAT SVs. Finally, Rab3a levels were similar in the three SV groups, while Rab3c levels were highest in VGLUT1–SVs. These quantitative results extend our previous studies on the differential expression of presynaptic proteins involved in neurotransmitter release in GABAergic and glutamatergic terminals and indicate that heterogeneity of the respective release machineries can be generated by the differential complement of SV proteins involved in distinct stages of the release process.